Semantics of names of the ancient Arabic pantheon representatives - Dunai, Katsiaryna V.; Isachenkova, Marina A. (Journal of the Belarusian State University. Philology, 2026)
Within the framework of the research, a linguocultural analysis of the names from the pre-Islamic Arabic pantheon has been conducted. The source material for the study includes texts of pre-Islamic poetry, as well as information from the work «The book of idols» by Hisham ibn al-Kalbi (8th century). The translation of fragments of pre-Islamic poems featuring theonyms, along with a commentary on them, is presented. The sources provide only the names of the deities without explanations or detailed descriptions of the characters. Based on the available sources, despite their limitations, it can be concluded that during the pre-Islamic period, Arabs had a relatively extensive but uncodified pantheon. The linguocultural approach helps clarify the semantics of the figures in the ancient Arabic pantheon.